Assessment of Antihyperlipidemic Properties of Aqueous Extract of Cassia Fistula Leaves (Medical Forum Monthly, 2024)
Objective: To study antihyperlipidemic properties of aqueous extract of Cassia fistula leaves in mice.Study Design: Experimental study.Place and Duration of Study: This study was conducted at Pharmacology Laboratory of Islamic International Medical College, Rawalpindi, and National Institute of Health, Islamabad from February to April 2011.Materials and Method: 40 male Balb/c mice were used which were randomly divided into 4 groups i.e. Group A, B, C and D, each group containing 10 mice. Duration of study was 8 weeks after acclimatization (1 week). Group A served as control group (received standard mice diet), Group B as disease control (received 2% cholesterol diet) and Group C & D as Cassia fistula groups (received 2% cholesterol diet + aqueous extract of Cassia fistula leaves 250 and 500 mg/kg respectively).Results: At the end of 8 weeks, blood samples of all the mice were analyzed. In disease Group B, there was significant rise in the levels of serum total cholesterol, triglycerides and LDL-C and decline in HDL-C. In Group C and D (Cassia fistula groups), there was much less rise in cholesterol, triglycerides and LDL-C especially in Group D. Also, there was significant increase in HDL-C level in group D.Conclusion: The results demonstrate that administration of aqueous extract of Cassia fistula leaves, along with cholesterol diet, not only prevented the rise in serum cholesterol, triglycerides and LDL-C levels but also increased the HDL-C level, demonstrating antihyperlipidemic properties of the extract.